There Were Also Many Women There : Lay Women in the Liturgical Movement in the United States, 1926-59 - Harmon, Katharine E. (Book collections on Project MUSE., 2012)
Where are the women in liturgical history? In considering the influential liturgical movement in the United States during the first half of the twentieth century, Katharine E. Harmon reveals that the reality is analogous to Matthew's account of the crucifixion of Jesus: "there were also many women there" (Matt. 27:55). In this groundbreaking study, Harmon considers women's involvement in the movement. Here, readers explore the contributions of Maisie Ward, Dorothy Day, Catherine de Hueck Doherty, Ade Bethune, Therese Mueller, and many others. Harmon shows how movements and institutions such as progressivism, Catholic women's organizations, Catholic Action, the American Grail Movement, and daily Catholic family life played a prominent role in the liturgical renewal. The historical record is clear that women were there, they ministered to the Mystical Body, and their important work must be recognized.